2004
DOI: 10.1159/000078762
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Reg Iα Protein in Human Gastric Cancers

Abstract: Background/Aims: Although regeneratinggene(Reg) Iα protein has a trophic effect on gastric epithelial cells, it is unclear whether Reg Iα protein and its receptor are involved in gastric carcinogenesis. Therefore, we investigated the Reg Iα protein expression in human gastric cancers and assessed its relationship to clinicopathological factors. Methods: Sixty-one gastric cancer specimens were examined, using immunohistochemistry, for Reg Iα protein, p53, and proliferating cell nuclear antigen. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…19 At present, REG family proteins are classified into four subfamilies according to their primary structures, 20 and their overexpression has been reported in neoplastic or inflamed tissues in various organs including the stomach, colorectum, bile duct, and pancreas. [5][6][7][8]14,21,22 Interestingly, microarray analyses suggest that expression of the REG Ia and REG IV genes is prominently upregulated during the development of gastric cancer, 10,11 and in fact we found immunohistochemically that not only REG Ia but also REG IV protein was overexpressed in a considerable number of gastric cancers. However, we also found that REG Ia and REG IV were not always coexpressed in a subset of gastric cancers.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…19 At present, REG family proteins are classified into four subfamilies according to their primary structures, 20 and their overexpression has been reported in neoplastic or inflamed tissues in various organs including the stomach, colorectum, bile duct, and pancreas. [5][6][7][8]14,21,22 Interestingly, microarray analyses suggest that expression of the REG Ia and REG IV genes is prominently upregulated during the development of gastric cancer, 10,11 and in fact we found immunohistochemically that not only REG Ia but also REG IV protein was overexpressed in a considerable number of gastric cancers. However, we also found that REG Ia and REG IV were not always coexpressed in a subset of gastric cancers.…”
Section: Discussionmentioning
confidence: 93%
“…5 In brief, 4-mm-thick sections were placed on slides, deparaffinized, and dehydrated. They were then placed in 0.01 mol/l citrate buffer (pH 6.0) and treated by microwave heating (MI-77; Azumaya, Tokyo, Japan; 400 W, 951C) for 10 and 40 min to facilitate antigen retrieval for REG Ia and Ki-67, respectively, whereas they received no treatment with microwave heating for the immunostaining of ssDNA.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…1 Thereafter, its human homologue REG Ia protein was suggested to be involved in the pathophysiology of gastrointestinal inflammation and its associated cancer. [2][3][4][5][6] Indeed, we previously reported that REG Ia protein behaves as a trophic and/or an anti-apoptotic factor in the development of colitis-or gastritis-associated cancer. 5,6 To clarify the regulatory mechanism of REG Ia gene expression, we initially screened major cytokines and showed that interleukin (IL)-6 and IFN-g are possible stimulators of REG Ia gene expression under inflammatory conditions.…”
mentioning
confidence: 99%